Tsunami history of an Oregon coastal lake reveals a 4600 yr record of great earthquakes on the Cascadia subduction zone - Kelsey, H. M.; Nelson, A. R.; Hemphill-Haley, E.; Witter, R. C. (Geological Society of America Bulletin, 2005)
Bradley Lake, on the southern Oregon coastal plain, records local tsunamis and seismic shaking on the Cascadia subduction zone over the last 7000 yr. Thirteen marine incursions delivered landward-thinning sheets of sand to the lake from nearshore, beach, and dune environments to the west. Following each incursion, a slug of marine water near the bottom of the freshwater take instigated a few-year-to-several-decade period of a brackish (<= 4 parts per thousand salinity) lake. Four additional disturbances without marine incursions destabilized sideslopes and bottom sediment, producing a suspension deposit that blanketed the lake bottom.Considering the magnitude and duration of the disturbances necessary to produce Bradley Lake's marine incursions, a local tsunami generated by a great earthquake on the Cascadia subduction zone is the only accountable mechanism. Extreme ocean levels must have been at least 5-8 m above sea level, and the cumulative duration of each marine incursion must have been at least 10 min. Disturbances without marine incursions require seismic shaking as well.Over the 4600 yr period when Bradley Lake was an optimum tsunami recorder, tsunamis from Cascadia plate-boundary earthquakes came in clusters. Between 4600 and 2800 cal yr B.P., tsunamis occurred at the average frequency of similar to 3-4 every 1000 yr. Then, starting similar to 2800 cal yr B.P., there was a 930-1260 yr interval with no tsunamis. That gap was followed by a similar to 1000 yr period with 4 tsunamis. In the last millennium, a 670-750 yr gap preceded the A.D. 1700 earthquake and tsunami. The A.D. 1700 earthquake may be the first of a new cluster of plate-boundary earthquakes and accompanying tsunamis.Local tsunamis entered Bradley Lake an average of every 390 yr, whereas the portion of the Cascadia plate boundary that underlies Bradley Lake ruptured in a great earthquake less frequently, about once every 500 yr. Therefore, the entire length of the subduction zone does not rupture in every earthquake, and Bradley Lake has recorded earthquakes caused by rupture along the entire length of the Cascadia plate boundary as well as earthquakes caused by rupture of shorter segments of the boundary. The tsunami record from Bradley Lake indicates that at times, most recently similar to 1700 yr B.P., overlapping or adjoining segments of the Cascadia plate boundary ruptured within decades of each other.
938hsTimes Cited:103Cited References Count:73